MENINGKATKAT KETERAMPILAN BERBICARA MELALUI KEGIATAN INFORMATION GAP PADA TARUNA PLLU STPI CURUG - Deni Sapta Nugraha (Langit Biru: Jurnal Ilmiah Aviasi, 2020)
The aim of this research was to investigate the implementation of information gap activity as teaching strategy to improve speaking skill of the fifth semester cadet of Indonesian Civil Aviation Institutes. This classroom action research was conducted to solve those problems occurring in the speaking class. In collecting the data, researcher uses speaking scoring rubric and field notes. This research was conducted in two cycles focusing on the improvement of the students’ speaking performance and their positive attitude to the implementation of the information gap activity (IGA) as teaching strategy in the speaking class. Research result revealed that the use of IGA could improve the students’ speaking performance and give them positive attitude to the implementation of some activities given. The findings showed that the average score of the students’ speaking performance could achieve 81.54 from the determined score 75. In addition, it was also found that 90 % of the students showed positive attitude to the implementation of IGA in the speaking class. The implementation of IGA as teaching strategy in speaking class can cover a procedure of six phases: eliciting, setting context, modeling, pairing, controlled practiced and semi freer practiced. Based on the findings, it is concluded that teaching speaking skill by using IGA can improve students’ fluency.